Penerapan Cooperatif Learning Tipe NHT pada Materi Sistem Reproduksi Manusia untuk Meningkatkan Hasil Belajar Siswa - Kustiyah, Kustiyah (Jurnal Studi Agama dan Masyarakat, 2009)
Classroom Action Research (CAR) is background by the thought of the need to overcome the passivity of students in the learning process, especially in the biological. Application of Cooperative Learning (CL) type of Numbered Heads Together (NHT) is an effort to find solutions to the problems faced by teachers in the learning, especially on the Human Reproduction System material. CAR aims to find out how the application of CL type NHT can improve student learning outcomes and how do the students respond to the CL type NHT. Learning outcomes of students who want to know include Understanding Concepts (UC) and Student Cooperative Skills (SCS). CAR involves 3 (three) as a biology teacher and research subjects are 34 students 1st XI Natural Sciences MAN Model Palangkaraya on Year 2007/2008 Lesson. Data obtained through written tests, observations and questionnaires. Instrument used is a test (multiple choice) and non-test (observation sheets and questionnaires). In addition to use other instruments such as the Learning Implementation Plan and Student Worksheet. Processing data used descriptive statistics, namely the present frequency distribution, averages, and percentages. The results showed that an increase in completeness UC after the application of CL type NHT of cycle I (24.3%), cycle II (32%), and the cycle III (54%). SCS that need to be maintained is A (located in the group) and B (to participate in tasks and discussion groups). SCS Â showed improvement SCS C (completing tasks on time), D (to show respect and sympathy) and F (asking questions / answers). SCS E (expressing disapproval/criticism) still needs to be increased and trained, as a percentage of the three cycles was low at 6% in cycle I, 12.5 %Â  in cycles II and 27% in cycle III. Meanwhile, students respond to the CL type NHT application is very positive (the response pattern agree 70.8% and 25.5% strongly agree).Â